AN OVERVIEW OF PEASANT FARMING - Vivak Ujjwal, Poonam Singh (International Journal of Modern Agriculture, 2021)
Peasant farming is a farming method that using small farming land from crop production without expensive technologies. As compared to commercial farming, it requires less machinery and small land for farming. There are various advantages of peasant farming including better supervision, more employment, greater productivity and possibility of quick decision in frequent weather and climate changes. Peasant farming is closely tied with more sustainable agriculture methods including hobby, organic, biodynamic and permaculture farms. Peasant farming plays a crucial role with an ever increasing demand for better food and the rise of health and wellness. By considering the importance of peasant farming, this review article discussed about the different aspects of the peasant farming such as peasant farmers, peasant seeds, merits and demerits followed by challenges associated with the peasant forming. Growth of the peasant farming will help to provide employment in rural areas and will also help in food productivity and quality.